Factors affecting community participation in environmental corporate social responsibility projects: Evidence from mangrove forest management project - Thirdchai Sattayapanich; Piyapong Janmaimool; Jaruwan Chontanawat (Journal of Open Innovation: Technology, Market, and Complexity, 2022)
Community participation in an environmental corporate social responsibility (CSR) project can help business enterprises effectively develop projects that respond to the actual demands of the community and effectively utilize a firm's resources. This study aims to investigate factors that affect community participation in each stage of environmental corporate social responsibility project development. The environmental corporate social responsibility project explored in this study is a sustainable mangrove forest management project in the Pakprasae sub-district of Rayong province in Thailand. This study has tested whether enterprise-related factors (such as perceived CSR credibility and organization-public relationship (OPR) quality) and participant-related factors (such as ecological knowledge, perceived ecological values, and expected benefits from participation in the project, both monetary and non-monetary related benefits) could predict community participation in an environmental corporate social responsibility project development initiated by a business enterprise. Questionnaire surveys were administered to 355 community members who were the target group of this environmental corporate social responsibility project from June to July 2022. The collected data were inspected and analyzed using an inferential statistical technique. Multiple regression analyses were performed to test significant factors that affected community members' participation in planning, implementing, and monitoring the project. The results revealed that perceived ecological values were the strongest predictor of participation in all stages of the project, including planning, implementing, and monitoring the project. Perceived CSR credibility and OPR quality also significantly affected participation in all stages, whereas ecological knowledge significantly affected participation only in the monitoring stage. These findings suggest that to promote community participation in each stage of environmental corporate social responsibility project development, it is important to enhance community members' perceived ecological values, and community members should be educated in ecology to enhance participation in the monitoring stage.
Keywords: 650; community engagement; ecological conservation; environmental corporate social responsibility; public participation; sustainable mangrove forest management